Prevalencia y factores de riesgo biológicos asociados al trastorno de hiperactividad e inatención en niños y niñas de 6 a 7 años de Segundo Año de Educación Básica en la Escuela Eliseo Álvarez de la ciudad de Loja periodo 2015. - Ludeña Jiménez, Joselin Zulay (2016)
The disorder of hyperactivity and inattention is a disorder involving biological factors, genetic and environmental, appears in childhood, is usually begin to diagnose around 7 years of age, although in some cases this diagnosis may be performed in a manner more precocious. Is manifested as an increase of physical activity, impulsivity and difficulty to maintain attention on an activity for a period of time continued. This is why this work is focused in the group of children of the school "Eliseo Alvarez" of our city, with the theme: PREVALENCE AND RISK FACTORS ASSOCIATED WITH THE BIOLOGICAL disorder of hyperactivity and inattention IN BOYS AND GIRLS OF 6 TO 7 YEARS OF SECOND YEAR OF BASIC EDUCATION IN THE SCHOOL "ELISEO ALVAREZ" IN THE CITY OF LOJA period 2015, whose general objective is to determine the prevalence and risk factors associated with this disorder biological, in children 6 to 7 years of school "Eliseo Alvarez". The research is descriptive and cross-sectional methodology used for data collection was through the questionnaire of Conners addressed to teachers and parents, it is used a survey to the mother of the family. The results, after made the whole process was a prevalence of hyperactivity of 15.9%; being male sex the most affected; it is evident that children of mothers exposed to biological risk factors postnatal Prenatal, Natal, and presented a higher prevalence of hyperactivity.In conclusion in the present study showed that there is a relation between the biological risk factors prenatal, natal, post-natal and the disorder of hyperactivity and inattention in children 6 to 7 years of school "Eliseo Alvarez" in the city of Loja. KEYWORDS: PREVALENCE, HYPERACTIVITY DISORDER AND INATTENTION,